Kolaborasi Antar Teman Sejawat untuk Menciptakan Pembelajaran yang Mendidik bagi Guru PAI di SMA Negeri 1 Kabila - Zulkarnain Ibrahim; Buhari Luneto; Habibie Yusuf (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study discusses the importance of collaboration among Islamic Religious Education (PAI) teachers at SMA Negeri 1 Kabila to improve the quality of educational teaching. This collaboration includes collaboration in designing and implementing student-oriented learning. Through this collaboration, PAI teachers exchange experiences, practices, and teaching innovations that are in accordance with the needs of students and the development of the times. The main objective of this study is to determine the implementation, supporting elements, and barriers to collaboration. The method used in this study is qualitative with interview, observation, and documentation techniques. The results of this study indicate that collaboration is carried out from the planning stage to implementation, including the creation of modules, media used, and teaching methods, as well as providing feedback to each other in the classroom. This collaboration not only improves the effectiveness of the teaching and learning process, but also helps teachers hone their competencies.